Diagnosis of pancreatic cancer by 2[18F]-fluoro-2-deoxy-D-glucose positron emission tomography. Issue 5 (May 1995) - Friess, H; Langhans, J; Ebert, M; Beger, H G; Stollfuss, J; Reske, S N; Büchler, M W
Abstract : The detection of pancreatic cancer or the discrimination between pancreatic cancer and chronic pancreatitis remains an important diagnostic problem. The increased glucose metabolism in malignant tumours formed the basis for this investigation, which focused on the role of positron emission tomography (PET) with 2[18F]-fluoro-2-deoxy-D-glucose (FDG) in the detection of pancreatic cancer and its differentiation from chronic pancreatitis. Eighty patients admitted for elective pancreatic surgery received preoperatively 250-350 mBq FDG intravenously and emission scans were recorded 45 minutes later. Intense focal activity in the pancreatic region was taken at the time of scanning as showing the presence of pancreatic cancer. The presence of cancer was later confirmed by histological examination of the surgical specimens and histological findings were compared with the preoperative PET results. Forty one patients with pancreatic cancer (group I: n = 42) had a focally increased FDG uptake in the pancreatic region. Two patients with a periampullary carcinoma (group II: n = 6) failed to develop FDG accumulation. In 28 patients with chronic pancreatitis (group III: n = 32) no FDG accumulation occurred. Overall sensitivity and specificity of PET for malignancy (group I + II) were 94% (45 of 48) and 88% (28 of 32), respectively. The standard uptake value of the patients with pancreatic carcinoma was significantly higher than in patients with chronic pancreatitis (3.09 (2.18) v 0.87 (0.56); p < 0.001; median (interquartile range)). These findings show that FDG-PET represents a new and non-invasive diagnostic procedure for the diagnosis of pancreatic cancer and to differentiate pancreatic cancer from chronic pancreatitis. However, the diagnostic potential of this technique requires further evaluation.